PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, KOMPETENSI APARATUR PEMERINTAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (Pada Organisasi Perangkat Daerah di K - Fauziyah, Euis Mardiyatul (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
AbstractThis study aims to examine the Influence of Regional Financial Accounting Systems, Competence of the Government Aaparatur, and Use of Information Technology on the Quality of Local Government Financial Reports with Internal Control Systems as moderating variables. The data used in this study is primary data. Methods of collecting data using questionnaires distributed to respondents. The questionnaire was distributed to 64 Serang City Government Organization employees involved in the process of preparing financial statements. The data analysis method used in this study is the Moderated Regression Analysis (MRA). The results of this study indicate that the influence of the Regional Financial Accounting System has a positive and significant effect on the quality of the Regional Government's Financial Statements, Competency of Government Officials does not have a positive and significant effect on the quality of the Regional Government's Financial Statements, and the Utilization of Information Technology has no positive and significant effect on the quality of the Government's Financial Statements. Area. The results of this study also indicate that the Internal Control System moderates the relationship between the Effects of the Regional Financial Accounting System, while the Internal Control System is not able to moderate the Effect of Competency of Government Apparatuses, and the Utilization of Information Technology on the Quality of Regional Government Financial Statements.Â AbstractThis study aims to examine the Influence of Regional Financial Accounting Systems, Competence of the Government Aaparatur, and Use of Information Technology on the Quality of Local Government Financial Reports with Internal Control Systems as moderating variables. The data used in this study is primary data. Methods of collecting data using questionnaires distributed to respondents. The questionnaire was distributed to 64 Serang City Government Organization employees involved in the process of preparing financial statements. The data analysis method used in this study is the Moderated Regression Analysis (MRA). The results of this study indicate that the influence of the Regional Financial Accounting System has a positive and significant effect on the quality of the Regional Government's Financial Statements, Competency of Government Officials does not have a positive and significant effect on the quality of the Regional Government's Financial Statements, and the Utilization of Information Technology has no positive and significant effect on the quality of the Government's Financial Statements. Area. The results of this study also indicate that the Internal Control System moderates the relationship between the Effects of the Regional Financial Accounting System, while the Internal Control System is not able to moderate the Effect of Competency of Government Apparatuses, and the Utilization of Information Technology on the Quality of Regional Government Financial Statements.